2009
DOI: 10.1021/ma901329n
|View full text |Cite
|
Sign up to set email alerts
|

Insoluble Patterns of Cross-Linkable Conjugated Polymers from Blend Demixing in Spin Cast Films

Abstract: Insoluble patterns of cross-linkable conjugated polymers, CPs, are obtained from spin coating their blends with polystyrene, PS, following an approach first demonstrated for poly [2-methoxy-5-(2 0 -ethyl)hexyloxy-2,4-phenylenevinylene] (MEH-PPV) by Castro et al. (Chem. Mater. 2006, 18, 5504). Taking advantage of the CP and PS tendency to phase separate, we make use of CP functionality to be crosslinked, so PS can be removed, leaving behind a solvent-resistant pattern. Columnar, spike, and porous structures can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 59 publications
0
37
0
Order By: Relevance
“…In particular, OPP has been extensively used in the cross‐linking of a wide range of oxetane‐functionalized conjugated polymers and small molecules, allowing, for instance, the fabrication of multilayer and pixelated OLED structures . In previous works, we have also shown the use of OPP to cross‐link oxetane‐functionalized copolymers of polyfluorenes and derivatives of P3HT . However, in the case of the P3HT system, we have observed a decrease of PV cells efficiencies upon cross–linking, which can be, at least in part, related to the presence of OPP (or its residues) in the active blends.…”
Section: Resultsmentioning
confidence: 74%
“…In particular, OPP has been extensively used in the cross‐linking of a wide range of oxetane‐functionalized conjugated polymers and small molecules, allowing, for instance, the fabrication of multilayer and pixelated OLED structures . In previous works, we have also shown the use of OPP to cross‐link oxetane‐functionalized copolymers of polyfluorenes and derivatives of P3HT . However, in the case of the P3HT system, we have observed a decrease of PV cells efficiencies upon cross–linking, which can be, at least in part, related to the presence of OPP (or its residues) in the active blends.…”
Section: Resultsmentioning
confidence: 74%
“…Porous films were prepared in three steps: (i) fabrication of films by spin‐coating PFC1/polystyrene (PS; M¯normaln = 3500) blend solutions onto quartz plates; (ii) photo‐crosslinking of the coumarin groups in the side chains of PFC1; and (iii) removal of PS from the cross‐linked blend films of PFC1/PS. In the first step, solutions of PFC1 (12 mg mL −1 ) and PS (12 mg mL −1 ) were prepared in toluene/THF (1:1 v/v), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This is among the highest PCEs reported for OPVs using crosslinked active layers. [34] In the context of oxetane functionalization, it is noteworthy that, although it is generally assumed that this mechanism requires the exposure to an acid, [14,35] Knauer et al [15] showed that crosslinking via oxetane groups can be achieved by prolonged heating, yielding a fully crosslinked and long-term stable BHJ cell.…”
Section: Application Of Crosslinking In Organic Photovoltaicsmentioning
confidence: 99%